Bd chaurasia's human anatomy regional and applied dissection and clinical : lower limb abdomen and pelvis - BD Chaurasia; Krishna Garg (New Delhi : CBS publishers, 2023)
This popular textbook encompasses the essence of the latest syllabus prescribed by Medical Council of India. All figures have been redrawn to improve lucidity, and many hand-drawn illustrations have been added to help students reproduced the details in their exams. Many new topics and features have been added to make this better than any other textbook in the market.
Includes index.
Keywords: Anatomy; Pelvis; Lower limb